1993
DOI: 10.1099/0022-1317-74-8-1673
|View full text |Cite
|
Sign up to set email alerts
|

Production of the M2 protein of influenza A virus in insect cells is enhanced in the presence of amantadine

Abstract: Recombinant baculoviruses that express the M2 protein from the genes of either the amantadine-sensitive, influenza A/Ann Arbor/6/60 virus or a laboratoryderived, amantadine-resistant mutant of this virus were constructed. Addition of amantadine or rimantadine at 2 ~tg/ml to cultures of Sf9 cells infected with the recombinant baculoviruses increased the yield of the M2 protein from the amantadine-sensitive virus approximately 10-fold, but did not increase the yield of the M2 protein from the amantadine-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Black et al (1993) reported a similar drug-induced enhancement of the expression of the M2 protein of influenza virus strain A/Ann Arbor/6/60, which differs from the Weybridge strain M2 by 15 amino acids (Ito et al, 1991). In contrast, amantadine treatment has no effect on M2 synthesis in virus-infected cells or M2 expression in mammalian cells or E. coli (F. Geraghty, A. Hayhurst & A. Hay, unpublished results).…”
Section: Discussionmentioning
confidence: 72%
“…Black et al (1993) reported a similar drug-induced enhancement of the expression of the M2 protein of influenza virus strain A/Ann Arbor/6/60, which differs from the Weybridge strain M2 by 15 amino acids (Ito et al, 1991). In contrast, amantadine treatment has no effect on M2 synthesis in virus-infected cells or M2 expression in mammalian cells or E. coli (F. Geraghty, A. Hayhurst & A. Hay, unpublished results).…”
Section: Discussionmentioning
confidence: 72%
“…[6][7][8] Emergence of amantadine-resistant strains Viral resistance to amantadine and its analogue rimantadine emerges quickly in vivo and in vitro. [1][2][3][4][5][9][10][11][12][13][14][15] Up to approximately one-third of patients may shed resistant viruses when amantadine or rimantadine is used for therapy. In vitro, sensitive viruses became resistant after three or five passages in the presence of 2 µg/ml amantadine.…”
Section: Action Of Amantadine Against Influenza a Virusesmentioning
confidence: 99%
“…Expression of the M 2 protein is deleterious to several host cell systems. Infection of Spodoptera frugiperda Sf9 cells with a recombinant baculovirus expressing the M 2 protein leads to inhibition of the replication of the recombinant baculovirus (1,26), and expression of M 2 protein in oocytes of X. laevis leads to premature cell death (5,13). In addition, expression of M 2 protein in Escherichia coli causes membrane permeability changes (6).…”
mentioning
confidence: 99%